Pilates for Overweight or Obesity: A Meta-Analysis - Wang, Yi; Chen, Zehua; Wu, Zugui; Ye, Xiangling; Xu, Xuemeng (Frontiers in Physiology, 2021)
Background: Evidence for the efficacy of Pilates for the modulation of body weight and body composition is unclear. Objective: This meta-analysis aimed to evaluate the effects of Pilates on body weight and body composition in adults with overweight or obesity. Data sources: The PubMed, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI) and EMBASE databases were systematically searched from the inception dates to November 12, 2020 for relevant randomized controlled trials (RCTs). Study selection: Randomized controlled trials comparing Pilates with other physical exercises or without any intervention were included. Data extraction and synthesis: Three reviewers independently performed the data extraction and assessed study quality. The mean differences (MDs) and 95% confidence intervals (CIs) for pooled data were calculated. Main outcomes and measures: Body weight, body mass index (BMI), body fat percentage, lean body mass and waist circumference. Results: Eleven RCTs with 393 subjects were included. This study revealed that Pilates dramatically reduces body weight (MD=-2.40, 95%CI: [-4.04, -0.77], P=0.004, I2=51%), BMI (MD=-1.17, 95%CI: [-1.85, -0.50], P=0.0006, I2=61%) and body fat percentage (MD=-4.22, 95%CI: [-6.44, -2.01], P=0.0002, I2=88%) in adults with overweight or obesity. The reduction in body weight and body fat percentage appears to be more pronounced in studies including participants with obesity only, and the efficacy of Pilates for the improvement of body weight and BMI appears to be more evident in longer intervention duration. However, Pilates has no significant effect on waist circumference (MD=-2.65, 95%CI: [-6.84, 1.55], P=0.22, I2=0%) and lean body mass (MD=-0.00, 95%CI: [-1.40, 1.40], P=1.00, I2=23%). Conclusions: Pilates dramatically reduces body weight, BMI and body fat percentage in adults with overweight or obesity. Large-scale and well-designed RCTs with improved methodology and reporting are urgently needed to further confirm these results.